2014
DOI: 10.7566/jpsj.83.013702
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Superconductivity on the Tetragonal Lattice in FeSe under Hydrostatic Pressure

Abstract: Superconductivity under pressure in FeSe (T c ∼7.5 K) has been investigated using singlecrystal specimens through the measurements of DC magnetization and electrical resistivity.A characteristic three-step increase in T c has been found under hydrostatic pressure up to ∼34 K above 7 GPa. The structural transition from a tetragonal phase to an orthorhombic phase (T s ∼87 K) is found to disappear at P ∼2.3 GPa, above which T c increases rapidly, suggesting that the superconductivity is enhanced by the tetragonal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 37 publications
9
80
3
Order By: Relevance
“…Before the disappearance of superconductivity it is clearly established that the Tc of FeSe first exhibits a plateau around 25 K in the 3-5 GPa range in polycrystalline samples, as concluded from magnetization and electrical resistivity measurements with the Daphne 7474 or Daphne 7373 oil as PTM 35 , or at 20 K in the 2.5-5 GPa range in single crystals pressurized with glycerol as PTM 20 . Then follows a strong increase, reported in several studies, with a maximum Tc around 6 GPa 36,20 (glycerol as PTM) or in the 6-8 GPa range 25,22 (argon gas as PTM). In all cases a decrease of Tc is found by further pressurization above this critical pressure 11,20,35 .…”
Section: High Pressure (P > 6 Gpa) Behavior Of Fese and Its Implicatimentioning
confidence: 65%
“…Before the disappearance of superconductivity it is clearly established that the Tc of FeSe first exhibits a plateau around 25 K in the 3-5 GPa range in polycrystalline samples, as concluded from magnetization and electrical resistivity measurements with the Daphne 7474 or Daphne 7373 oil as PTM 35 , or at 20 K in the 2.5-5 GPa range in single crystals pressurized with glycerol as PTM 20 . Then follows a strong increase, reported in several studies, with a maximum Tc around 6 GPa 36,20 (glycerol as PTM) or in the 6-8 GPa range 25,22 (argon gas as PTM). In all cases a decrease of Tc is found by further pressurization above this critical pressure 11,20,35 .…”
Section: High Pressure (P > 6 Gpa) Behavior Of Fese and Its Implicatimentioning
confidence: 65%
“…For example, chemical substitution with sulfur or tellurium also suppresses T s , but slightly increases T c for low substitution values 30 . Similarly, hydrostatic pressure decreases T s and increases T c initially 27,31,32 . Recently, it was shown that a dose of 2.5 MeV electron irradiation producing approximately ∼ 0.1% Frenkel pairs per formula unit, decreases T s by 0.9 K and increases T c by 0.4 K (Ref.…”
Section: Resistance: Results and Discussionmentioning
confidence: 99%
“…The superconducting transition temperature, T c , is non-monotonic, -increasing initially up to 0.8 GPa, then decreasing, reaching a minimum at 1. 3 GPa and increasing again [24][25][26]. Despite the absence of LRMO, a strong nematic response is found in FeSe, and has been discussed in terms of both spin and orbital fluctuations [27][28][29][30][31].…”
mentioning
confidence: 99%